Analisis Implementasi Tata Letak Fasilitas Pada Proses Produksi Gula Pasir Di PT. Perkebunan Nusantara XIV Takalar Kabupaten Takalar - Karmila Karmila; Muh aris pasigai; Asdar Asdar (Universitas Muhammadiyah Makassar, 2019)
This research is conducted to describe how the implementation of facilities layout on sugar production process. The type of research conducted is descriptive qualitative research, which intends to collect data and information about the problems and reality at the place of research according to what is obtained at the time of research. Research conduction in PT. Perkebunan Nusantara XIV Takalar takalar district production section by selecting a resource consisting of two informants namely the head of the department and one of the employees of the processing. Data collection techniques used are interview techniques, observation and documentation techniques. The results of research that has been done that the layout is applied to the factory takalar sugar is the layout in groups by the management that can streamline the time in the production process and facilitate the supervision of the production process went smoothly